Repairability of a 3D printed denture base polymer: Effects of surface treatment and artificial aging on the shear bond strength. (February 2021) - Li, Ping; Krämer-Fernandez, Pablo; Klink, Andrea; Xu, Yichen; Spintzyk, Sebastian
Abstract: Objectives: The present study aimed to evaluate the repairability of a 3D printed denture base material. The effects of surface treatments and artificial aging on the shear bond strength (SBS) were investigated. Methods: A total of 224 specimens were printed by digital light processing technology (Rapid Shape D30II) using a 3D printing denture base material (FREEPRINT denture). To evaluate the repairability, the SBS and failure modes were measured after surface treatment and artificial aging. Specifically, half of the specimens were further performed with thermocycling (5–55 °C, 5000 cycles) for artificial aging. The aged and non-aged specimens were further divided into four subgroups (n = 28) to simulate a denture base repair with one of the following treatments: control (without surface treatment), monomer (applying methylmethacrylate for 120 s), P600 (grinding with P600 silicon carbide paper) and sandblasting (blasted with 125 μm aluminum oxide with 2 bar), respectively. Surface roughness was measured (n = 6) and surface topography was observed by scanning electron microscopy (n = 2). A test rod was built on the sample surface using the same 3D printing material. Afterward, all specimens further underwent thermocycling (5–55 °C, 10, 000 cycles). Results: For non-aged groups, no significant differences in SBS could be found (p < 0.05), and bondings failed cohesively in the denture base material. Regarding the aged control and monomer group, adhesive failures at the interface were primarily observed, and SBS values were statistically lower than those of the other groups (p < 0.05). Conclusions: The 3D printed denture base material exhibited favorable repairability. For the realignment surface, the SBS at the bonding interface is satisfying and additional surface treatments could be not necessary. In contrast, the aged surface could significantly decrease the SBS; hence subtractive surface treatments are highly recommended. Graphical abstract: Image 1 Highlights: Repairability of a 3D printed denture base material was investigated. Surface treatment had no effect on the shear bond strength for non-aged samples. The superficial aged layer could decrease the shear bond strength. Applying subtractive surface treatments on aged surfaces is highly recommended. 3D printed denture base material showed favorable repairability.